Majas Gaya Bahasa pada Lirik Lagu “Asmalibrasi”: Analisis Gaya Bahasa dan Stilistika (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The purpose of making this journal is to find out the meaning of the lyrics of the song "Asmalibrasi" then the next goal is to find out what language styles or figure of speech are contained in the lyrics of the song "Asmalibrasi" and some of our goals, especially in this song, are devoted to teenagers who are in love. tried to proceed to a more serious stage, namely marriage but the couple had doubts because of the many problems that arose but the couple was finally able to proceed to the marriage stage because by lowering their respective egos. The theory we use is according to several well-known experts. The method we use in this journal is by listening to the song and reading the lyrics to the song. The result of our analysis is that each lyric of the song “Asmalibrasi” contains many meanings that we must learn. Our recommendation is to be careful in choosing each partner, not because of the standard of society.